Formulation and characterization of banana fruitcake - Zulla, Mary Janilee Calusay (2008.)
Three local varieties of banana namely Balangon (B), Saba (S), and Latundan (L) were tested for banana fruitcake production.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Banana; Fruitcake